Relationship between morphometric traits and predictive models for total skin length in slaughtered South African Nile Crocodiles (Crocodylus niloticus corviei) - Rachuene, Pretty (My University, 2025)
Nile crocodiles are common in South Africa, reaching up to 6m in total length. The quality and yield of crocodile skins plays a significant role in it price determination Hence, the aim of this study was to determine the relationship between the total skin length and measurable skin traits viz skin weight (SW), skin thickness (ST), neck total length (NTL), neck width at the top (NWT), neck width at the middle (NWM), belly width (BW), belly length (BL), total tail length (TTL), tail length from the middle (TLM), and tail width (TLW). The first objective was to determine the phenotypic relationship between total skin length and measurable skin traits of the Nile crocodile. The second objective was to establish a model for predicting the total skin length of the Nile crocodile from measurable skin traits. A total of 180 crocodile skins from 35 months old Captive-bred Nile crocodiles, sourced from Lalele Crocodile Farm, were used for data collection. Data was analysed via Statistical Package for Social Sciences (SPSS), software version 29.0. The first objective was achieved using Pearson’s correlation. The second objective was achieved using simple linear regression and multiple regression analysis. Correlation results indicated that TSL was correlated with SW (0.81), NTL (0.37), BW (0.75), BL (0.79), TTL (0.87), TLM (0.78), TLW (0.48), NWM (0.60), NWT (0.51) at p<0.01 and ST (0.17) at p<0.05. Regression findings showed that, as a single trait, TTL was the best predictor of TSL, as shown by the highest coefficient of determination (0.76) and RMSE (31.98). Furthermore, regression analysis showed that model 1 (TSL = 16.35 + 4.68SW + 1.28ST + 1.03BL + 0.39BW + 0.81TTL + 0.13TLM - 0.25TLW + 0.21NTL + 0.19NWT – 0.14NWM) had the highest coefficient of determination (R2 = 0.90) and the lowest residual mean square error (RMSE = 14.28) and would reliably predict TSL of Nile crocodiles. The results suggest there is a positive relationship between the total skin length and measurable skin traits of Nile crocodile and improving these traits might improve TSL. Skin traits such as SW, NTL, NWT, BW, BL, TTL, TLM, TLW, and ST may be used to improve TSL. TTL may be used to easily predict TSL. These findings may aid in better management and selection for breeding of Nile crocodiles for improved skin yield and quality.
Thesis (M.Sc. Agriculture (Animal Production)) -- University of Limpopo, 2025
Keywords: Skin morphometrics; Crocodilian; Skin quality; Total tail length; Skin yield; Nile crocodiles; Crocodylus; Crocodiles; Crocodiles -- Identification; Hides and skins